Pengaruh Massage Effleurage Abdomen terhadap Penurunan Nyeri Dismenore pada Mahasiswi Kebidanan di Poltekes TNI AU - Eti Sukmiati; Tenang Juvita Sitepu; Herli Herlina (Pusat Riset dan Inovasi Nasional, 2026)
Dysmenorrhea , menstrual pain that radiates to the back and thighs, can affect anyone before and after menstruation. The causes are diverse, ranging from an unbalanced diet to stress. However, there is hope to overcome it. Recent research shows that non-pharmacological techniques or abdominal effleurage massage can significantly reduce dysmenorrhea pain by increasing oxygen levels in tissues and reducing pain. This study aims to determine the effect of abdominal effleurage massage on reducing dysmenorrhea pain in midwifery students at Poltekes TNI AU Ciumbuleuit. The research design used a quasi-experimental approach with a two-group pretest-posttest design, involving 16 students who experienced dysmenorrhea, selected using random sampling technique. Data analysis used the Wilcoxon Signed Rank Test. The results showed that before the intervention, 3 participants (37.5%) experienced severe pain and 5 participants (62.5%) experienced moderate pain. After the intervention, there was a decrease in pain levels, with 5 participants (62.5%) experiencing moderate pain and 3 participants (37.5%) experiencing mild pain. The Wilcoxon Signed Rank Test analysis showed a significant effect between abdominal effleurage massage and reduction of dysmenorrhea pain (p < 0.05). This study provides new hope for those seeking non-pharmacological solutions to overcome dysmenorrhea. For future researchers, it is expected that they can further develop this method and explore other types of non-pharmacological therapies.